Cleavage of poly(A)-binding protein by duck hepatitis A virus 3C protease. Issue 1 (December 2017) - Sun, Di; Wang, Mingshu; Wen, Xingjian; Cheng, Anchun; Jia, Renyong; Sun, Kunfeng; Yang, Qiao; Wu, Ying; Zhu, Dekang; Chen, Shun; Liu, Mafeng; Zhao, Xinxin; et al.
Abstract During viral infections, some viruses subvert the host proteins to promote the translation or RNA replication with their protease-mediated cleavage. Poly (A)-binding protein (PABP) is a target for several RNA viruses; however, the impact of duck hepatitis A virus (DHAV) on PABP remains unknown. In this study, we demonstrated for the first time that DHAV infection stimulates a decrease in endogenous PABP and generates two cleavage fragments. On the basis ofin vitro cleavage assays, an accumulation of PABP cleavage fragments was detected in duck embryo fibroblast (DEF) cell extracts incubated with functional DHAV 3C protease. In addition, DHAV 3C protease was sufficient for the cleavage of recombinant PABP without the assistance of other eukaryotic cellular cofactors. Furthermore, using site-directed mutagenesis, our data demonstrated a 3C protease cleavage site located between Q367 and G368 in duck PABP. Moreover, the knockdown of PABP inhibited the production of viral RNA, and the C-terminal domain of PABP caused a reduction in viral replication compared to the N-terminal domain. Taken together, these findings suggested that DHAV 3C protease mediates the cleavage of PABP, which may be a strategy to manipulate viral replication.